2004
DOI: 10.1016/j.ijindorg.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Shirking and motivations in firms: survey evidence on worker attitudes

Abstract: A framework on worker motivations is tested with an extensive US survey; 82.7% of the respondents report that they are very likely to keep an agreement to work hard, even if it was almost impossible for their employer to monitor them. Based on mean responses, the rank order of motivations is moral, intrinsic, peer pressure, and positive incentives. Respondents also report that fairness considerations are important and that they are especially likely to keep agreements with honest employers. Logit analysis indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…This is not without reason: the importance of monetary incentives for workers' motivation is confirmed in many empirical studies, see Prendergast (1999) However, monetary incentives are often not considered as the most important motivator by workers and managers. Many workers consider task enjoyment and moral concerns as stronger motivators than monetary incentives (Minkler 2004). In a study on managers' use of motivational tools, Agell (2004) reports that more than 60% of managers in Sweden use 'good management-worker relations' to a great or fairly great extent.…”
Section: Introductionmentioning
confidence: 99%
“…This is not without reason: the importance of monetary incentives for workers' motivation is confirmed in many empirical studies, see Prendergast (1999) However, monetary incentives are often not considered as the most important motivator by workers and managers. Many workers consider task enjoyment and moral concerns as stronger motivators than monetary incentives (Minkler 2004). In a study on managers' use of motivational tools, Agell (2004) reports that more than 60% of managers in Sweden use 'good management-worker relations' to a great or fairly great extent.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, considerable evidence indicating that people often act contrary to their material self-interest (Frey and Jegen, 2001;Fehr et al, 2002;Gintis et al, 2003;Fehr and Rockenbach, 2003). Moreover, the assumption that workers will shirk in the absence of sufficient incentives is one for which there is little empirical evidence (Minkler, 2004). The evidence points to the existence of informal norms and sociopsychological forces that may often motivate workers more powerfully than financial incentives do (Baron 1988).…”
Section: Section Iii: Non-materialistic Motivation Introductionmentioning
confidence: 99%
“…However, in recent years more and more economists have been using the findings of social sciences on the nature of work motivation, taking their analysis to a more sophisticated level than that offered by the strict material self-interest postulate (e.g. Frey, 1993Frey, , 1997Kreps, 1997;Murdock, 2002;Bénabou and Tirole, 2003;Minkler, 2004). The importance of this is captured well by Gibbons (1998: 130), who observed that "one simple possibility is that economic models that ignore social psychology may be incomplete (but perhaps still useful) descriptions of incentives in organizations.…”
Section: Section Iii: Non-materialistic Motivation Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a survey by Minkler (2004) indicates that shirking in firms may not be as much of a problem as suggested by standard economic theory (see, e. g., Eaton and White, 1983). According to his results, moral and intrinsic motivation are very important determinants of workers' behavior.…”
Section: Empirical Evidencementioning
confidence: 86%